Aile hukukumuzda boşanma sebebi olarak pek kötü ve ağır derecede onur kırıcı davranış - Ersoy, Arzu (My University, 2010)
TEZ ÖZETİ Boşanma evlenme akdedildikten sonra, kanunen belirli bazı sebeplerin bulunması halinde eşlerden birinin veya her ikisinin talebi ile hakimin evlenmeye son vermesidir. Boşanma konusunda boşanmayı yasaklayan, boşanmanın serbest olmasını kabul eden ve boşanmayı belirli sebeplerin varlığı halinde hakim hükmü ile gerekleşebileceğini kabul eden üç farklı yaklaşım- sistem bulunmaktadır. Boşanma sebeplerinindayandığı ilkeler; kusur, irade, temelden sarsılma, elverişsizlik ilkeleridir. Medeni Kanun’umuzdaki boşanma sebepleri zina, hayata kast, pek kötü veya onur kırıcı davranış, suç işleme ve haysiyetsiz yaşam sürme, terk, akıl hastalığı ve evlilik birliğinin sarsılmasıdır. Acımasızca dövme, aç bırakmak, aşırı derecede cinsel ilişkide bulunmak pek kötü davranışa örnek eylemlerdir. Pek kötü davranışa yönelik hareket kasıtlı olarak eşlerden biri tarafından diğerine yönelik olarak gerçekleştirilmeli ve eylemin niteliği itibarı ile eşin beden yapısı üzerinde tahrip edici, ona acı ve eziyet veren yoğunlukta olması (pek kötü nitelikte) olması gereklidir. Evlilik birliğinde eşler birbirlerinin onurlu şekilde yaşama haklarına saygı göstermek, bu hakkın ihlali sayılabilecek davranışlarından kaçınmak zorundadırlar. Eşin toplumda küçük düşürülmesi, küçümsenmesi, başkalarıyla ilişkisi olduğuna dair dedikodular çıkarılması, eşe hakaret edilmesi ağır derecede onur kırıcı davranışa örnektir. Pek kötü veya ağır derecede onur kırıcı davranış sebebiyle boşanma davasında davacı davranışa maruz kalan eş, davalısı ise davranışı gerçekleştiren eştir. Davada görevli mahkeme Aile Mahkemeleri, yetkili mahkeme ise eşlerden birinin yerleşim yeri veya davadan önce son defa altı aydan beri birlikte oturdukları yer mahkemesidir. Davaya hakkı olan eşin boşanma sebebini öğrenmesinden başlayarak altı ay ve her halde bu sebebin doğumunun üzerinden 5 yıl geçmekle dava hakkı düşer. Ayrıca, af halinde dava hakkının ortadan kalkar. THESIS

Divorce is a legal act whereby a marriage is dissolved by a decree of court upon the request of either or both of the spouses in cases which constitute legal grounds for divorce. There are three basic approaches to divorce; an approach proclaiming the indissolubility of marriage, the other approach supporting that divorce should be legal and a fault-based divorce approach. The grounds for divorce depend primarily on fault, irretrievable breakdown of marriage and incompatibility. Turkish Civil Code recognizes adultery, plot against life, grave assaults, and insults; crime or a dishonorable life, desertion, mental infirmity and incompatibility as being grounds for divorce. Unmercifully beating, cruelly starving, excessive sexual demands or abnormal sexual intercourse are a few examples of bad or evil conduct. Spousal abuse can be broadly defined as a pattern of abusive behaviors (involving abuse and/ or humiliating) by one of the spouses including but not limited to intentional act of aggression or mistreatment or cruelty towards the other that causes pain, misery and suffering and/ or in a way which is severely detrimental to his or her body or honor. In conjugal community spouses should respect each other’s right to live a honorable and dignified life and should refrain from any act that may be considered as a violation of this right. Public humiliation of or humiliating the spouse in presence of others, degradation of the spouse, gossiping to others about the spouse complaining that he/ she has an intimate relationship with another woman/ man and insulting the spouse are examples of maltreatment or severely insulting behavior In divorce cases based on the grounds of maltreatment or severely insulting behavior the plaintiff party is the spouse who has been subject to such maltreatment or severely insulting behavior and the defendant party is the spouse who has severely maltreated or insulted his/ her spouse. Family courts have jurisdiction over divorce actions whereas the Court in charge located in the place where one of the spouses has his/ her residence, or in the last place where the spouses lived together at least for a period of six months before the case is filed shall be authorized to deal with the divorce case. The suit must be brought within six months from the date when the injured party becomes aware of grounds for divorce, and in any event within five years from the date of occurrence of the event giving rise to a claim for divorce. The right of action is lost where the innocent party has forgiven the guilty party.
Keywords: Aile Hukuku; Hukuk; Özel Hukuk